Антиоксидантний потенціал рослин родин Brassicaceae Burnett та Poaceae Barnhart. - Vergun, O.M.; Rakhmetov, D.B. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2018)
Objective – to estimate the antiradical scavenging ability of extracts of some plants of Brassicaceae Burnett and Poaceae Barnhart. species, to evaluate the total antioxidant activity of plants in the conditions of M.M. Gryshko National Botanical Garden of the NAS of Ukraine. Material and methods. Plant material of this investigation – species, varieties and cultivars of Brassicaceaae and Poaceae families: Brassica campestris f. annua D.C. (BCA), B. campestris f. biennis D.C.× B. napus f. biennis D.C., cv. Innovatsiia (BCBNI), B. campestris f. biennis D.C. × B. rapa L. × B. napus f. biennis D.C. (BCBRBN), B. juncea (L.) Czern. (BJ), B. juncea (L.) Czern. f. biennis, cv. Annushka (BJA), B. napus f. biennis D.C., f. EROF-5 (BNE-5), B. rapa L. (BR), B. rapa subsp. rapifera Metzger (BRR), Raphanus sativus L. var. oleiformis Pers. (RSO), Miscanthus sacchariflorus (Maxim.) Benth., cv. Snihopad (MSS), M. sinensis Anderss. f. ESBMK-6 (MSE-6), Panicum virgatum L. f. PB (PVPB), P. virgatum L. f. PL (PVPL), Sorghum bicolor (L.) Moench. f. ETSSDF-11 (SBE-11), S. nigrum Roemer et Schultes f. ETSSCHF-1 (SNE-1), S. saccharatum (L.) Moench. cv. Medove (SSM), S. sudanense (Piper) Stapf (SS), S. technicum (Koern.) Bait. et Trab. (ST). The antioxidant activity of methanol and aqueous extracts based on the discoloration reaction on the solution of DPPH (2,2-diphenyl-1-picrylhydrazyl free radical) was determined according to Brandt-Williams et al. The determination of content of ascorbic acid was conducted according to V.P. Krishchenko, the content of carotene – according to B.P. Pleshkov. Results. The antioxidant activity of methanol extracts of plants of Brassicaceae was registered in the range from 16.94±0.15 (BCA) to 36.91 ± 0.26 (BRR) % and aqueous extracts – from 26.53 ± 0.34 (BJ) to 65.85 ± 0.30 (RSO) %. This parameter for methanol extracts of Poaceae species was in range from 31.13 ± 0.32 (MSE-6) to 86.48 ± 0.49 (SNE-1) % and aqueous extracts – from 33.10 ± 0.47 (ST) to 83.14 ± 0.46 (PVPB) %. It was determined concentration of ascorbic acid from 118.67 ± 9.90 (BJA) to 566.61 ± 38.37 (BNE-5) mg% and carotene – from 0.48 ± 0.01 (BJA) to 3.11 ± 0.07 (BJ) mg% for Brassicaceae plants. Content of ascorbic acid in range from 11.80 ± 0.85 (PVPB) to 77.39 ± 1.29 (SS) mg% and carotene – from 0.05 ± 0.00 (PVPB) to 0.62 ± 0.02 (PVPL) mg% was identified for Poaceae plants. Conclusions. This study showed that plant raw material of investigated plants is a valuable source of antioxidants and vitamins. Methanol and water extracts of plants of Poaceae had higher antiradical activity against DPPH radical than extracts of plants of Brassicaceae. The higher level of ascorbic acid and carotene was observed in extracts of plants of Brassicaceae. The minimal content of ascorbic acid and carotene found for BJA (Brassicaceae) and PVPB (Poaceae).